IMRAS—A clinical trial of mosquito-bite immunization with live, radiation-attenuated P. falciparum sporozoites: Impact of immunization parameters on protective efficacy and generation of a repository of immunologic reagents - Hickey, Bradley; Teneza-Mora, Nimfa; Lumsden, Joanne; Reyes, Sharina; Sedegah, Martha; Garver, Lindsey; Hollingdale, Michael R.; Banania, Jo Glenna; Ganeshan, Harini; Dowler, Megan; Reyes, Anatalio; Tamminga, Cindy; et al. (PloS one, 2020)
Immunization with radiation-attenuated sporozoites (RAS) by mosquito bite provides >90% sterile protection against Plasmodium falciparum (Pf) malaria in humans. RAS invade hepatocytes but do not replicate. CD8+ T cells recognizing parasite-derived peptides on the surface of infected hepatocytes are likely the primary protective mechanism. We conducted a randomized clinical trial of RAS immunization to assess safety, to achieve 50% vaccine efficacy (VE) against controlled human malaria infection (CHMI), and to generate reagents from protected and non-protected subjects for future identification of protective immune mechanisms and antigens. Two cohorts (Cohort 1 and Cohort 2) of healthy, malaria-naïve, non-pregnant adults age 18-50 received five monthly immunizations with infected (true-immunized, n = 21) or non-infected (mock-immunized, n = 5) mosquito bites and underwent homologous CHMI at 3 weeks. Immunization parameters were selected for 50% protection based on prior clinical data. Leukapheresis was done to collect plasma and peripheral blood mononuclear cells. Adverse event rates were similar in true- and mock-immunized subjects. Two true- and two mock-immunized subjects developed large local reactions likely caused by mosquito salivary gland antigens. In Cohort 1, 11 subjects received 810-1235 infected bites; 6/11 (55%) were protected against CHMI vs. 0/3 mock-immunized and 0/6 infectivity controls (VE 55%). In Cohort 2, 10 subjects received 839-1131 infected bites with a higher first dose and a reduced fifth dose; 9/10 (90%) were protected vs. 0/2 mock-immunized and 0/6 controls (VE 90%). Three/3 (100%) protected subjects administered three booster immunizations were protected against repeat CHMI vs. 0/6 controls (VE 100%). Cohort 2 uniquely showed a significant rise in IFN-[gamma] responses after the third and fifth immunizations and higher antibody responses to CSP. PfRAS were generally safe and well tolerated. Cohort 2 had a higher first dose, reduced final dose, higher antibody responses to CSP and significant rise of IFN-[gamma] responses after the third and fifth immunizations. Whether any of these factors contributed to increased protection in Cohort 2 requires further investigation. A cryobank of sera and cells from protected and non-protected individuals was generated for future immunological studies and antigen discovery.